Hand Surgery in New Zealand - Patel, Sandeep C.; Smith, Karen; Mohammed, Khalid D. (Journal of Hand and Microsurgery, 2020)
Hand surgery in New Zealand has steadily grown from its origins in plastic surgery and orthopaedic surgery into its own discipline. There has been much progress and innovation in hand surgery that has originated from New Zealand and this review acknowledges the historical figures and events that have led to our present position. The current and future directions of hand surgery in our country are also discussed. As a small and remote country, we are very fortunate to have close relationships with other international hand societies. Through these relationships and the efforts of committed regional hand surgeons, the art and science of hand surgery in New Zealand continues to progress.
Keywords: hand surgery; orthopaedic surgery; plastic surgery